Lentiviral nef proteins utilize PAK2-mediated deregulation of cofilin as a general strategy to interfere with actin remodeling - Stolp-Rastätter, Bettina; Abraham, Libin; Rudolph, Jochen M.; Fackler, Oliver Till (Journal of virology, 2010)
Nef is an accessory protein and pathogenicity factor of human immunodeficiency virus (HIV) and simian immunodeficiency virus (SIV) which elevates virus replication in vivo. We recently described for HIV type 1SF2 (HIV-1SF2) the potent interference of Nef with T-lymphocyte chemotaxis via its association with the cellular kinase PAK2. Mechanistic analysis revealed that this interaction results in deregulation of the actin-severing factor cofilin and thus blocks the chemokine-mediated actin remodeling required for cell motility. However, the efficiency of PAK2 association is highly variable among Nef proteins from different lentiviruses, prompting us to evaluate the conservation of this actin-remodeling/cofilin-deregulating mechanism. Based on the analysis of a total of 17 HIV-1, HIV-2, and SIV Nef proteins, we report here that inhibition of chemokine-induced actin remodeling as well as inactivation of cofilin are strongly conserved activities of lentiviral Nef proteins. Of note, even for Nef variants that display only marginal PAK2 association in vitro, these activities require the integrity of a PAK2 recruitment motif and the presence of endogenous PAK2. Thus, reduced in vitro affinity to PAK2 does not indicate limited functionality of Nef-PAK2 complexes in intact HIV-1 host cells. These results establish hijacking of PAK2 for deregulation of cofilin and inhibition of triggered actin remodeling as a highly conserved function of lentiviral Nef proteins, supporting the notion that PAK2 association may be critical for Nef's activity in vivo.